Research of pre-match preparations pattern of excellent canoe slalom athletes in the world - Peng, J.-z.; Li, X.; Sun, Y.-l.; Zhang, L.; Zhang, G. (Journal of Beijing Sport University, 2012)
Pre-match preparation is not only a high degree of reflection of the project characteristics, but also is an important prerequisite for successful competition of athletes. Based on questionnaires and interviews, firstly, the study analyzes two basic units about cognitive activity and functional activity before preparation of the canoe slalom. And then, according to the characteristics of the canoe competition, it compares with difference between the sequence structure of the single-round tournament preparation activities with the sequence structure of the two race preparations. Finally, according to the results of follow-up survey, it studies the mode of excellent world canoe slalom athlete's preparation patterns of pre-competition activity.